Recirculation of the Canary Current in fall - Espino Falcón, Elisabet (2015)
CTD and LADCP data measured in October 2014 are used to describe water masses, geostrophic circulation and mass transport in the Eastern Boundary of the North Atlantic Subtropical Gyre. Initial geostrophic velocities are adjusted to velocities from the LADCP data to estimate an initial velocity at the reference layer. Final reference velocities and consequently circulation is estimated from a box inverse model applied to an ocean divided into 12 neutral density layers. This allows us to evaluate mass fluxes consistent with the thermal wind equation and mass conservation. Ekman transport derived by the Weather Research and Forecasting (WRF) model is added to the first layer and adjusted from the inverse model. The Canary Current transports a net mass of 3.8±0.7 Sv (1 Sv=106 m3/s≈109 kg/s) of North Atlantic Central Water southward at thethermocline layers (0-700 m). The Canary Current recirculates northward at a rate of 4.8±0.8 Sv at the thermocline layers between the Lanzarote Island and African coast (Lanzarote Passage). The Canary Current extends to the intermediate layers transporting southward 1.9±0.6 Sv of a mixture of Mediterranean Water and Antarctic Intermediate Water. Separately, at intermediate layers, Antarctic Intermediate Water flows northward at a rate of 2.4±0.6 Sv through the Lanzarote Passage.